STUDI KOORDINASI OCR DAN GFR SALURAN DISTRIBUSI PENYULANG SANDA UNTUK MENINGKATKAN KONTINUITAS PELAYANAN - I Putu Gede Aras Widya Pratama; I Gede Dyana Arjana; Cok. Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2021)
The Sanda feeder is supplied by Antosari Substation through transformer unit II and ithas 3 reclosers, they are pempatan recloser,bangsing recloser and palisan recloser. Based onthe 2017 disturbance fault recapitulation data from PT PLN (Persero) Bali, it has been phasephaseand 1-phase ground short circuit in Sanda feeders almost every month. One of theproblems that often occurs in Sanda Feeders is when a phase-phase and 1-phase ground faultoccurs at the end of the feeder network and causes simultaneous trips to the recloser at thebase of feeder network, causing the Sanda feeder relay to blackout. This shows the systemneed to analyze the evaluation of the coordination settings for the OCR and GFR protectionsystem on the recloser and Sanda Feeder relays to minimize disturbances so as to improveservice continuity. The analysis and simuation results represent that, the existing settingconditions of OCR and GFR has coincide coordination curves and the grading time is still below0.3 seconds. The calculation and simulation of OCR and GFR that are carried out show that theprotection system works selectively in the absence of coincide coordinating curves and a timegrading value above 0.3 seconds according to the IEC 60255 standard.